EVALUATION OF DIFFERENT CONCENTRATIONS OF TARZEC AND AXIAL HERBICIDES AND SEEDING RATES ON WHEAT (TRITICUM AESTIVUM L.) GROWTH, YIELD, AND WEED CONTROL - Dheyaa Aljuburi; Moyassar Aziz; Ammar Sami; Hameed Alsamadany; Abeer Kutby (Mesopotamia Journal of Agriculture)
The study is conducted during the winter season of season 2022-2023 in two locations, Al-Jarn village/Nimrud district/Nineveh Governorate and Bartella district, to evaluate the efficiency of concentrations of herbicides "TARZEC" and "AXIAL" and seeding rates on the growth and yield of wheat and accompanying weed, The results showed that the seeding rate of 160 kg h1 recorded the best seed rate for the number weight weed, number of weeds, the number grains, the number spikes, and the grain yield amounted to 6.03, 2.05 weed.m2, 3.38, 6.61 g.m2, 38.59, 37.17 grain.spike1, 504.1, 474.1 spike.m2, and 578.73, 516.06 g.m2 for the above traits and for both locations respectively. weed control efficiency in weeds number and weight TARZEC 100% and AXIAL 100% was 65.3%, 60.94%, 64.4%, 51.54%, 55.74%, 53.0%, 46.53% and 49.44% for both locations respectively. the highest rate of the number of grains in spike, the number of spikes and the yield of grains was recorded with the TARZEC  100%, TARZEC+25, AXIAL 100% and AXIAL +25. Conclude from the above that the best seeding rate is 160 kg.h in addition to the use of herbicides "TARZEC" and "AXIAL" in the recommended concentrations.